Dynamic-Mechanic Analysis and Rheological Modelling of Waste Face Mask Modified Bitumen - Ozdemir, Ahmet Munir; Yalcin, Erkut; Yilmaz, Mehmet; Kok, Baha Vural (Turkish Chamber Civil Engineers, 2024)
Due to the Covid-19 global pandemic, the use of face masks has increased considerably in recent years. Used face masks are released into our environment and become a severe environmental threat. Therefore, researchers have focused on the recycling of waste face masks. Recently, studies have been carried out on the use of waste face masks as additives in bituminous materials, but a detailed rheological characterization has not been made. In this study, modified bitumens were obtained by adding 1%, 1.5%, 2%, 2.5%, and 3% waste face mask (WFM). Subsequently, frequency sweep test was performed on modified bitumen samples through a Dynamic Shear Rheometer (DSR). Thus, the viscoelastic behavior of WFM modified bitumen was investigated at different temperatures and loading rates. Performance analysis was conducted with rheological master curves, which were characterized according to analytical and mechanistic models. In this study, rheological evaluations were performed according to the Christensen-Anderson (CA) Model, Christensen-Anderson-Marasteanu (CAM) Model, Sigmoidal Model (SM), and finally, the mechanistic Huet-Sayegh Model (HSM). According to the results, it was determined that WFM significantly increased the rutting resistance of bitumen and performed better at low and high loading rates than the pure bitumen at each WFM ratio.
Keywords: Bitumen; waste face mask; dynamic shear rheometer; rheology; huet-sayegh model